The double marginalisation: reflections on young women and the youth crisis in Sub-Saharan Africa - Vasconcelos, Joana (2011)
There has been an upsurge in academic studies on youth in Sub-Saharan Africa since the last decade of the 20th century, underlining the growing importance that generational cleavages seem to play in today’s societies. However, gender has been neglected in research and policies bearing on youth, unveiling a rather negative and limited approach to Sub-Saharan African youth: limit situations are those most focused on (as the role of youth in conflicts), young males being perceived as the most active in those contexts and who therefore shall be the focus of political (and academic) attention. Acknowledging the need to integrate gender in the approaches to youth, this paper tries to grasp, through a preliminary literature review, how the predicaments of the so-called “youth crisis” are lived and perceived by young girls, and identify the main themes and theoretical perspectives of the literature that has tried to explore this thematic.